Characteristics and Predisposing Factors of Bacterial Corneal Ulcer in the National Eye Center, Cicendo Eye Hospital, Bandung from January to December 2011 - Astrid Maharani Putri; Susi Heryati; Nursiah Nasution (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Corneal ulcer is an emergency condition in ophthalmology, causing visual impairment, mostly by bacterial infection with rapid pathogenesis. The aim of this study was to discover the characteristics of bacterial corneal ulcer patients in the National Eye Center, Cicendo Eye Hospital, Bandung.Methods: A total of 99 medical records consisted of patients diagnosed with bacterial corneal ulcer were selected in this descriptive study. The clinical patterns and predisposing factors of the patients were analyzed. The study also identified the pathogenic bacteria of the cases. This study was carried out in the National Eye Center, Cicendo Eye Hospital, Bandung from January to December 2011 Clinical patterns. The collected data were analyzed and presented in frequency tabulation.Results: The male to female ratio was 2:1, with the average age of 44.4 years. The most common presenting symptom was eye pain (70.7%). Most patients came with decreased visual acuity that was categorized as (near-) blindness (78.8%) and the location of the ulcer was in central area of the cornea (56.5%). The most common predisposing factor was ocular trauma (74.7%) that was caused by exposed to plants. Single-bacterial infection (67.7%) was predominant, with 56 cases (56.6%) of Gram-positive cocci infection.Conclusions: Bacterial corneal ulcer contributes to 48.8% of all microbial corneal ulcers. Most patients came with mild condition, centralized location, and poor visual function. The common predisposing factor was trauma associated with exposed to plants. DOI: 10.15850/amj.v2n3.505